Characteristics and Correlation of Indonesian Cabin Crew Marital Status and Anxiety 2022 - Augisna, Fadhilah Qostholani; Theresa, Ria Maria; Lardo, Soroy; Herardi, Ryan; Savitri, Pritha Maya (Universitas Airlangga, 2024)
Introduction: Fear of getting COVID-19 has led to an upsurge in mental health problems, particularly among those who deal directly with others, such as cabin crew. A regulation has been established requiring travelers to attach the results of a COVID-19 test to prevent the transmission of the virus during flight. While the number of confirmed COVID-19 cases continued to rise, the regulations were subsequently repealed in early 2022. The marital status of an individual is one factor that can influence the level of anxiety. Studies regarding the correlation between marital status and anxiety levels of cabin crew during the COVID-19 pandemic in Indonesia are still lacking. This study aims to determine the correlation between marital status and anxiety levels of Indonesian cabin crews in 2022. Methods: In November 2022, a cross-sectional offline survey was conducted using a written questionnaire. Using consecutive sampling with inclusion and exclusion criteria, a final sample of 79 was analyzed. The independent variable is classified as either married or unmarried based on Indonesia Law Act No. 1 of 1974. Anxiety levels, the dependent variable, were collected using a Hamilton Anxiety Rating Scale (HARS) questionnaire and a personal data questionnaire. Results: A correlation was observed between the marital status of Indonesian cabin attendants in 2022 and their anxiety levels (p=0.025), according to the findings. Conclusion: Increased anxiety levels about cabin personnel's marital status are driven by the worry of catching COVID-19, which will result in feelings of loneliness, particularly for cabin crew with unmarried marital status